Studi Observasional Identifikasi Bahaya Kesehatan Kerja pada Pekerja Pengelasan Kapal MV. KAREEM di PT. Samudra Marine Indonesia Tahun 2025 - Haikal Rafi Widyadhana; Desyawati Utami; Cut Aliya Keumala Muda; Devi Angeliana Kusumaningtiar (Pusat riset dan Inovasi Nasional, 2025)
Welding work on ships carries high risks of health disturbances due to exposure to heat, smoke, chemicals, and poor ergonomic work positions. This study aims to identify potential occupational health hazards among welders working on the MV KAREEM ship at PT. Samudra Marine Indonesia in 2025. The study uses a descriptive observational design with total sampling technique, involving 30 welders. Data were collected through direct observation using observation sheets and documentation in accordance with the welding SOP. The results of the study revealed five categories of health hazards. Physical hazards included excessive heat, noise, and poor lighting. Chemical hazards included welding fumes, metal dust, and toxic gases. Biological hazards arose from exposure to microorganisms in the work environment. Ergonomic hazards were related to awkward posture, prolonged static positions, and manual handling loads. Psychosocial hazards included long working hours, high workload, and conflicts among workers. The findings emphasize that welders are prone to health disturbances due to various risk factors. Preventive measures, including improving the work environment, implementing stricter safety standards, and providing occupational health education, are essential to reduce these risks.